Instructional materials for teaching English idioms to Ilocano high school students - Dumlao, Dorotheo C. 1932- ([Quezon City s.n., 1972)
This paper endeavored to construct instructional materials based on the linguistic difficulties and other problems encountered by Ilocano learners of English in learning the correct and effective use of English idiomatic verbs. It has also offered several recommendations designed to improve further the teaching of English as a second language, particularly to Ilocano students.
Thesis (M.A.T.)--University of the Philippines.
Keywords: English language -- Idioms, corrections, errors -- Study and teaching; Teaching aids and devices